2018
DOI: 10.1021/acs.jnatprod.8b00565
|View full text |Cite
|
Sign up to set email alerts
|

Amarisolide F, an Acylated Diterpenoid Glucoside and Related Terpenoids from Salvia amarissima

Abstract: Nine terpenoids were isolated from the leaves and flowers of Salvia amarissima, including a new acylated diterpenoid glucoside, amarisolide F (1), a new neo-clerodane diterpenoid, amarissinin D (2), which was isolated as an acetyl derivative (2a), and four known diterpenoids. The structure of amarisolide F (1) was elucidated by NMR and MS data analyses, as well as its methanolysis products 7 and 8, which also constituted new diterpenoids, named amarissinin E and 8-epi-amarissinin E, respectively. The absolute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 13 publications
0
6
0
2
Order By: Relevance
“…Three of these were preliminarily identified as terpene compounds, which could be inferred by their positive reaction to ceric sulphate, in which the color observed changed from purple to red. Plants of this family (Lamiaceae) contain a high quantity of terpenoids (monoterpenes, diterpenes, and triterpenes) [37][38][39][40], as in the case of S. amarissima, having been identified as neo-clerodane diterpenes, such as amarisolides, amarissinins, and teotihuacanine [24][25][26]38,41].…”
Section: Discussionmentioning
confidence: 99%
“…Three of these were preliminarily identified as terpene compounds, which could be inferred by their positive reaction to ceric sulphate, in which the color observed changed from purple to red. Plants of this family (Lamiaceae) contain a high quantity of terpenoids (monoterpenes, diterpenes, and triterpenes) [37][38][39][40], as in the case of S. amarissima, having been identified as neo-clerodane diterpenes, such as amarisolides, amarissinins, and teotihuacanine [24][25][26]38,41].…”
Section: Discussionmentioning
confidence: 99%
“…The structures of the isolated compounds were established by the analyses of their NMR spectroscopic and MS spectrometric data and were compared with those described in the literature (Nagao et al 2002;Gecibesler et al 2019). Curiously, during the isolation procedure, sesquiterpenoids and diterpenoids were not isolated as is common in Salvia species (Bautista et al 2017;Fragoso-Serrano et al 2019). The subsequent evaluation of the antiprotozoal properties of isolates 1-3 showed that compounds 1 and 2 had moderate antiprotozoal activity against both protozoa, with IC 50 values of 40.4 (40.9-39.8) and 42.7 (43.1-41.8) μM against E. histolytica; and 61.6 (66.1-60.4) and 60.3 (62.1-59.4) μM against G. lamblia, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Phytochemical studies of S. circinata have reported the presence of diterpenoids such as amarissinins A-E (Bautista et al 2016, Fragoso-Serrano et al 2019 and teotihuacanin (Bautista et al 2015, Fragoso-Serrano et al 2019, and glucoside diterpenoids as amarisolides A-F (Maldonado et al 1996, Flores-Bocanegra et al 2017, Fragoso-Serrano et al 2019. Flavonoids like pedalitin (Maldonado et al 1996), apigenin-7-O-β-D-glucoside, the flavone 2-(3,4-dimethoxyphenyl)-5,6-dihydroxy-7-methoxy-4H-chromen-4-one, and new biflavone (Flores-Bocanegra et al 2017).…”
Section: High Performance Liquid Chromatography (Hplc-dad)mentioning
confidence: 99%